1999
DOI: 10.1021/ja990263x
|View full text |Cite
|
Sign up to set email alerts
|

Life and Death of an Active Ethylene Polymerization Catalyst. Ligand Involvement in Catalyst Activation and Deactivation. Isolation and Characterization of Two Unprecedented Neutral and Anionic Vanadium(I) Alkyls

Abstract: Reaction of {2,6-bis[2,6-(i-Pr)2PhNC(Me)]2(C5H3N)}VCl3·1.3(CH2Cl2) (1) with stoichiometric amount of methyl alumoxane (PMAO) in toluene resulted in the methylation of the pyridine ring ortho position affording {2,6-bis[2,6-(i-Pr)2PhNC(Me)]2(2-MeC5H3N)}VCl2·0.5 (toluene) (2). In the process the ligand became an anionic amide, one chlorine atom was eliminated by the metal center, and the vanadium coordination number decreased by one unit. This new trivalent compound is a potent ethylene polymerization precatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
203
2
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 209 publications
(213 citation statements)
references
References 34 publications
6
203
2
2
Order By: Relevance
“…ortho-Iminopyridines (IMPY, Scheme 3) were originally sampled as ligands for olefin polymerization catalysis, without any recognition of their redox potential. [19,20] However, there has been growing recognition that certain of the examples in Scheme 3 can be redox-active, [21] and others probably await exploitation in this regard. For example, the ortho-iminopyridines have been shown to be richly redox-active.…”
Section: Discussionmentioning
confidence: 99%
“…ortho-Iminopyridines (IMPY, Scheme 3) were originally sampled as ligands for olefin polymerization catalysis, without any recognition of their redox potential. [19,20] However, there has been growing recognition that certain of the examples in Scheme 3 can be redox-active, [21] and others probably await exploitation in this regard. For example, the ortho-iminopyridines have been shown to be richly redox-active.…”
Section: Discussionmentioning
confidence: 99%
“…When the temperature was raised from 60 to 70 , the PDI value decreased with the decreasing low molecular weight polyethylene (Run 12). The active species produced from the bis(imino)pyridinevanadium complex was investigated by Reardon et al 6) . They reported that the in-situ reaction of 2,6-[2,6-(i-Pr)2PhN C(CH3)]2C5H3NVCl3 and MAO on the pyridine ring resulted in the formation of the methylated complex, 2,6-[2,6-(i-Pr)2PhN C(CH3)]2(2-CH3C5H3N)VCl2, through elimination of one chlorine atom.…”
Section: Resultsmentioning
confidence: 99%
“…Among the transition metal complexes having a bis(imino) pyridine backbone, the bis(imino)pyridinevanadium(III) complexes have been investigated, because these combined with MAO show a significant activity for the polymerization or oligomerization of ethylene 6)~16) . Moreover, as remarkable properties, these complexes promoted the copolymerization of ethylene and α-olefin 6) , and the supported catalysts using a modified magnesium chloride can produce high-molecular weight polyethylene 13) . When metal complexes are used for most of the industrial polymerization processes, they must be immobilized on carriers.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, there is no correlation of selectivity with product stability. The C3 and C4 adducts are usually similar in energy and much more stable than any of the other adducts, but so far C3 addition has only been observed in two rather exceptional cases (Ca, [8] V [9] ). In contrast, the much less stable C2-alkylation product seems to form easily, and the pyridine N-alkylation product has been observed for Li, Mg and Zn.…”
Section: Ligand Alkylation Reactionsmentioning
confidence: 96%